Interstitial lung diseases in the hospitalized patient - Disayabutr, Supparerk (BMC Med, 2015)
BACKGROUND: Interstitial lung diseases (ILDs) are disorders of the lung parenchyma. The pathogenesis, clinical manifestations, and prognosis of ILDs vary depending on the underlying disease. The onset of most ILDs is insidious, but they may also present subacutely or require hospitalization for management. ILDs that may present subacutely include acute interstitial pneumonia, connective tissue disease-associated ILDs, cryptogenic organizing pneumonia, acute eosinophilic pneumonia, drug-induced ILDs, and acute exacerbation of idiopathic pulmonary fibrosis. Prognosis and response to therapy depend on the type of underlying ILD being managed. DISCUSSION: This opinion piece discusses approaches to differentiating ILDs in the hospitalized patient, emphasizing the role of bronchoscopy and surgical lung biopsy. We then consider pharmacologic treatments and the use of mechanical ventilation in hospitalized patients with ILD. Finally, lung transplantation and palliative care as treatment modalities are considered. SUMMARY: The diagnosis of ILD in hospitalized patients requires input from multiple disciplines. The prognosis of ILDs presenting acutely vary depending on the underlying ILD. Patients with advanced ILD or acute exacerbation of idiopathic pulmonary fibrosis have poor outcomes. The mainstay treatment in these patients is supportive care, and mechanical ventilation should only be used in these patients as a bridge to lung transplantation.